Efficacy and safety of bromfenac 0.075% formulated in DuraSite for pain and inflammation in cataract surgery. (22nd September 2019) - Wentz, Scott M; Price, Francis; Harris, Alon; Siesky, Brent; Ciulla, Thomas
ABSTRACT: Introduction : Bromfenac is a topical ophthalmic non-steroidal anti-inflammatory drug (NSAID) used to reduce pain and treat post-operative inflammation after cataract surgery. Bromfenac 0.075% in the DuraSite™ vehicle is a newly-approved formulation which has been shown to be efficacious and safe for use in cataract surgery to reduce pain and treat inflammation. It has been shown to have a slightly better posterior segment ocular bioavailability compared to similar topical ophthalmic NSAIDs. However, there is a paucity of studies investigating its role in the prevention and treatment of post-operative pseudophakic cystoid macular edema. Areas covered : In this review, the authors provide an overview of similar products available, describe the novelty of bromfenac 0.075% in the DuraSite vehicle, and discuss the relevant clinical studies to determine if the formulation is safe and efficacious. Expert opinion : Bromfenac 0.075% in the DuraSite vehicle is a new topical ophthalmic medication which has been approved by the FDA for the prevention of pain and treatment of post-operative inflammation. It provides cataract surgeons with an additional medication for cataract surgery. However, no robust studies have been performed showing the effect that it has on the reduction or prevention of post-operative pseudophakic cystoid macular edema.